2017
DOI: 10.1111/jpi.12410
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin administration to wild‐type mice and nontreated NLRP3 mutant mice share similar inhibition of the inflammatory response during sepsis

Abstract: The NLRP3 inflammasome is involved in the innate immune response during inflammation. Moreover, melatonin blunts the NF-κB/NLRP3 connection during sepsis. Thus, we compared the roles of the NLRP3 inflammasome and/or melatonin treatment in the septic response of wild-type and NLRP3 mice. Mouse myocardial tissue was used for this purpose. The nuclear turnover of NF-κB was enhanced during sepsis, with an increase in TNFα, iNOS, and pro-IL-1β. The lack of inflammasome in NLRP3 mice significantly reduced that respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 81 publications
(121 reference statements)
1
71
0
Order By: Relevance
“…Melatonin treatment not only prevented the increase in the number of macrophages but also blocked the induction of IL‐1β and components of the NLP3‐inflammasome in the adenohypophysis. In agreement with our results, prevention of NLP3‐inflammasome activation by melatonin has been demonstrated in inflammatory diseases and sepsis . In harmony with these results, melatonin has been shown to favor the anti‐inflammatory M2 phenotype over M1 in liver Kupffer cells, peritoneal macrophages, and splenocytes from stressed mice …”
Section: Discussionsupporting
confidence: 92%
“…Melatonin treatment not only prevented the increase in the number of macrophages but also blocked the induction of IL‐1β and components of the NLP3‐inflammasome in the adenohypophysis. In agreement with our results, prevention of NLP3‐inflammasome activation by melatonin has been demonstrated in inflammatory diseases and sepsis . In harmony with these results, melatonin has been shown to favor the anti‐inflammatory M2 phenotype over M1 in liver Kupffer cells, peritoneal macrophages, and splenocytes from stressed mice …”
Section: Discussionsupporting
confidence: 92%
“…Studies have identified that NF‐κB could bind to TLR4 and NLRP3 promoter region, suggesting the transcriptional regulation of NF‐κB on TLR4 and NLRP3 and its downstream targets . Furthermore, melatonin could suppress NF‐κB‐dependent pro‐inflammatory mediators in various cell types . From these findings, we surmise that melatonin may participate in the regulation of NLRP3 inflammasome by modulating the NF‐κB signal in adipocytes.…”
Section: Discussionmentioning
confidence: 66%
“…Melatonin has shown protective effect on BBB integrity via a variety of pathways: inhibition of the toll like receptor 4 (TLR4)/NF-κB signaling pathway in neonatal rats (Hu et al, 2017), inhibition of NADPH oxidase-2 (Jumnongprakhon et al, 2016), inhibition of MMP-9 (Alluri et al, 2016), inhibiton of AMP-activated protein kinase (AMPK) activation (Wang et al, 2017) and impact on silent information regulator 1 (SIRT1; Zhao et al, 2015) and NLRP3 inflammasome (Rahim et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Aging and sepsis triggered NLRP3 inflammasome activation (Volt et al, 2016), which has been shown to be involved in the innate immune response during inflammation (Rahim et al, 2017). Furthermore, NLRP3 inflammasome activation was showed to be associated with the upregulation of apoptotic signaling pathway in various inflammatory diseases (Volt et al, 2016) and melatonin attenuated subarachnoid hemorrhage-induced BBB damage via attenuating the expressions of NLRP3 (Dong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%